Greening Gunung Wangi: An Alternative for Village Tourism Development in Bangkel Hamlet - Andika Andika; Geraldo Yesaya Toatubun; Wildan Mustahiqul Amri; Naomi Safira Ekawati; Monika Sastria Yuliana Ema; Wiwin Syaputri Ningsih; Imana Dien Rifata; Hangga Catur Prasetyo; Gilang Vitra Sejati; Hilebrodus Alfin Rivaldo Bere; Emanuel Gosa; Samsin Budiman; Budi Setyanta (Altifani Journal: International Journal of Community Engagement, 2023)
Gunung Wangi has excellent potential to be developed as an attractive tourist destination. With its mesmerizing sunset and nighttime beauty and its status as an affordable tourist option, Gunung Wangi can be a valuable alternative to rural tourism options in Bantul. However, the challenges faced, such as the lack of vegetation leading to an arid feel and the lack of comfort, require serious attention. As a solution, a reforestation initiative has been implemented, resulting from a collaboration between a community service team from Janabadra University, Gunung Wangi managers, and the Yogyakarta Watershed Management Center. The reforestation initiative was designed as a sustainable approach, hoping to provide long-term benefits to the environment and the local community. The implementation process of this PKM was organized in several stages. These stages include problem identification, socialization of the reforestation program with residents and administrators of Gunung Wangi, submission of tree seedlings to the Yogyakarta Watershed Management Agency (BPDAS), and tree planting activities at Gunung Wangi. The results of this activity not only positively impacted Gunung Wangi's environment but also raised the awareness of the community and students on the importance of environmental conservation. In addition, it encourages their active role in maintaining ecological balance. Hopefully, these efforts will ensure that Gunung Wangi is known for its beauty and as a symbol of successful environmental conservation.